Effects of an interpersonal style intervention for coaches on young soccer players` motivational processes - Pulido, J. J.; Sanchez-Oliva, D.; Leo, F. M.; Matos, S.; Garcia-Calvo, T. (Journal of Human Kinetics, 2017)
The main goal of the study was to assess the effects of an intervention programme developed with soccer coaches, based on promoting strategies to optimise the satisfaction of the basic psychological needs of athletes. Eight soccer coaches, aged between 19 and 50 years (M = 32.5; SD = 14.34), participated in the study. They were selected intentionally (without academic or federative training) and divided equally into a control and an experimental group by random peer selection. Also, 109 soccer players, aged between 11 and 15 years (M = 13.78; SD = 1.38), divided into a control group (CG; n = 56) and an experimental group (EG; n = 53), participated in the experiment. The training programme (12 hours) was aimed to develop methodological and motivational strategies to promote autonomy, competence and relatedness need satisfaction among the players. The results showed that the participants in the EG decreased competence and relatedness control, while significantly increased (post-intervention) competence and relatedness needs satisfaction. Moreover, values for the EG did not decrease for autonomy, competence frustration and amotivation, while they increased for the sport commitment. Also, intrinsic motivation decreased in both groups (greater decrease in the CG). In conclusion, we can affirm the effectiveness of the training programme to create an environment of "bright side" motivation, and reduce thwarting styles, needs frustration and low self-determination levels.